Synthesis, characterization, and properties of new 3‐hexyl‐2, 5‐diphenylthiophene: Phenylene vinylenes copolymers as colorimetric sensor for iodide anion. Issue 24 (13th February 2017) - Mansha, Muhammad; Sohail, Manzar; Ullah, Nisar
ABSTRACT: Four new conjugated copolymersP1 ‐P4 have been prepared by the Horner‐Emmons and Knoevenagel polymerization reactions.P1 ‐P4 were characterized by NMR, FTIR, cyclic voltammetry (CV), diffuse reflectance UV–vis spectroscopy (DR UV–vis), and thermal gravimetric analysis (TGA). The optical band gaps of these polymers, calculated from the onset absorption edge, were found between 2.15 and 2.34 eV. The band gaps calculated by CV were ranged between 1.94 and 2.57 eV. The presence of nitrile moiety on the phenylene vinylene unit is believed to influence the optical properties of these polymers, i.e., P3 andP4 have shown lower band gaps thanP1 andP2 . All polymers possess good iodide anion sensing property over a wide range of other anions (F −, Cl −, Br −, NO 3 −, CN − ), indicating their promise in fabricating selective iodide sensors. The initial colorless solution of polymers in THF changed to deep yellow upon the addition of aqueous solution of iodide salts along with significant changes in the UV–vis spectra of the polymers. The limit of detection (LOD) forP1‐P4 were found between 0.43 and 2.54 m M . These polymers constitute long alkoxy and alkyl side chains, bearing excellent solubility in most common organic solvents which warrants their suitability for photovoltaic devices application. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44948. Abstract :